Simulation study of micelle formation by bile salts - Vila Verde, A. (2010)
We report coarse-grained, implicit-solvent simulations of aqueous solutions of bile salts. The parameters in our model were optimized to reproduce some of the experimentally known behavior of dihydroxy bile salts at “physiological” temperature and counterion concentration. We find that micelle formation in dihydroxy and trihydroxy bile salts is only weakly cooperative in the sense that there is barely a free energy barrier that stabilizes these micelles against disassembly. Bile molecules are found to pack in many different orientations in pure bile micelles. Both features may be physiologically relevant: the ability to pack in different orientations may be necessary to form mixed micelles with nutrients of a wide range of molecular lengths and shapes, and the reduced micelle stability may facilitate nutrient release once the mixed micelles reach the intestinal wall.